Haploinsufficiency of Dspp Gene Causes Dentin Dysplasia Type II in Mice - Shi, Ce; Ma, Ning; Zhang, Wei; Ye, Jiapeng; Shi, Haibo; Xiang, Danwei; Wu, Chunyue; Song, Lina; Zhang, Ning; Liu, Qilin (Frontiers in Physiology, 2020)
Dentin dysplasia (DD) and dentinogenesis imperfecta (DGI) patients have abnormal structure, morphology, and function of dentin. DD-II, DGI-II, and DGI-III are caused by heterozygous mutations in the dentin sialophosphoprotein (DSPP) gene in humans. Evidences have shown that loss of function of DSPP in Dspp knockout mice leads to phenotypes similar to DGI-III, and that the abnormal dentinogenesis is associated with decreased levels of DSPP, indicating that DSPP haploinsufficiency may play a role in dentinogenesis. Thus, to testify the haploinsufficiency of Dspp, we used a Dspp heterozygous mouse model to observe the phenotypes in the teeth and the surrounding tissues. We found that Dspp heterozygous mice displayed dentin phenotypes similar to DD-II at the ages of 12 and 18 months, which was characterized by excessive attrition of the enamel at the occlusal surfaces, thicker floor dentin of the pulp chamber, decreased pulp volume, and compromised mineralization of the dentin. In addition, the periodontium was also affected, exhibiting apical proliferation of the junctional epithelium, decreased height and width of the alveolar bone, and infiltration of the inflammatory cells, leading to the destruction of the periodontium. Both the dental and periodontal phenotypes were age-dependent, which were more severe at 18 months old than those at 12 months old. Our report is the first to claim the haploinsufficiency of Dspp gene and a DD-II mouse model, which can be further used to study the molecular mechanisms of DD-II.